Repeated inhibition of sigma-1 receptor suppresses GABAA receptor expression and long-term depression in the nucleus accumbens leading to depressive-like behaviors - Qin, Yaoyao; Xu, Weixing; Li, Kunpeng; Luo, Qi; Chen, Xi; Wang, Yue; Chen, Lei; Sha, Sha (Frontiers in Molecular Neuroscience, 2022)
Sigma-1 receptor (σ1R) downregulation in male mice is known to cause a depressive-like phenotype. The nucleus accumbens (NAc), a region associated with affective regulation, has high levels of σ1R. Here, we investigated the effect of repeated inhibition of σ1R in the NAc on depressive-like behaviors and synaptic plasticity by microinjecting σ1R antagonist NE-100 into NAc nuclei in mice (NE-100 mice); this was followed by behavioral tests and field potentials recordings. We first examined the effect of NE-100 administration on σ1R expression and found that cell surface levels of σ1R were significantly reduced in the NAc of NE-100 mice. Compared to control mice, NE-100 mice exhibited significantly prolonged immobility in forced swim test (FST) and tail suspension test (TST), impaired long-term depression (LTD) as well as multi-spike waveform field excitatory postsynaptic potential (fEPSP) with an extended duration and an increased paired-pulse ratio (PPR). Reduced levels of GABAA receptor (GABAAR)-α1, -α2, -β2, and -β3 subunits, membrane D2R, and PKC phosphorylation in the NAc were observed in NE-100 mice. Activation of GABAAR by muscimol corrected the extended fEPSP duration and increased PPR, restored LTD maintenance as well as alleviated depressive-like behaviors in NE-100 mice. The decline of PKC phosphorylation in the NAc of NE-100 mice was corrected by injecting NAc with quinpirole, a D2R agonist. Injections of quinpirole or PMA (a PKC activator) into NAc of NE-100 mice rescued the expression levels of GABAAR, and alleviated the increase in PPR and impairment in LTD; these effects were sensitive to GF109203X, a PKC inhibitor. Furthermore, injecting NAc with quinpirole or PMA relieved depressive-like behaviors in NE-100 mice. Collectively, these results indicate that repeated inhibition of σ1R in the NAc reduces D2R-mediated PKC phosphorylation and suppresses GABAAR expression, thus impairing LTD maintenance and leading to depressive-like behaviors.